Praktik Bagi Hasil Pengelolaan Lahan Perkebunan Kelapa Sawit pada Koperasi Cempaka Biru Kecamatan Sejangkung Kabupaten Sambas Perspektif Hukum Islam - Arifin, Zarul (Institut Agama Islam Negeri Curup, 2020)
This research is motivated by the practice of profit sharing in the management of land by cooperatives in the absence of time clarity in the distribution of results carried out by cooperatives to their members. Islam towards the practice of sharing the results of land management by the Cempaka Biru Cooperative in the Sejangkung District. This type of research is a type of descriptive qualitative research that is Field Research (field research). The study uses a normative sociological approach. The data source in this study uses primary data taken from the cooperative chairman, treasurer and cooperative members. Whereas the secondary data sources are books, mass media and the Law. Data collection techniques used were observation techniques, interview techniques, and documentation techniques. Based on the results of the study, the researchers concluded that the practice of sharing the results of land management by the Cempaka Biru Cooperative did not violate Law No. 25 of 1992 article 45 concerning Remaining Results of Operations, because basically the residual results of cooperative efforts are cooperative income obtained in one fiscal year. In the analysis according to the perspective of Islamic law the profit-sharing in the Cempaka Biru Cooperative is called the profit sharing of theÂ MusaqahÂ plantation estate orÂ mukhabarah. But the practice of sharing the results of land management by the Cempaka Biru Cooperative in the District of Sejangkung is prohibited by syara 'because of the existence of a contract containing the element of gharar (uncertainty) so that it is prohibited by syara'.